Hubungan aktifitas fisik dengan kejadian hipertensi pada lansia - Nusaibah, Nusaibah; Suryani, Suratini (JOURNAL OF Community Health Issues, 2024)
Backgorund: Hypertension is known as the "silent killer" because it often presents without symptoms but can lead to fatal complications such as stroke, heart attack, and kidney failure. According to data from the Indonesian Ministry of Health in 2023, hypertension is the fourth leading cause of death in Indonesia, accounting for 10.2% of total deaths. The elderly are the most vulnerable group to hypertension, especially in rural areas. One contributing factor to the increasing incidence of hypertension among the elderly is a low level of physical activity, which negatively affects cardiovascular and metabolic function. Purpose: To determine the relationship between physical activity and the incidence of hypertension among the elderly in Dadapbong Village, Sendangsari, Pajangan, Bantul. Method: This was a quantitative study using a descriptive correlational design with a cross-sectional approach. The population consisted of elderly individuals in Dadapbong Village, with a sample of 81 people selected through random sampling. Data were collected using the Global Physical Activity Questionnaire (GPAQ) and a sphygmomanometer to measure respondents' blood pressure. Data analysis was conducted using the non-parametric Kendall Tau test. Results: The statistical analysis showed a p-value < 0.05, specifically 0.000 for the relationship between physical activity and hypertension. Conclusion: indicating a significant relationship between physical activity and the incidence of hypertension among the elderly in Dadapbong Village, Sendangsari, Pajangan, Bantul. It is recommended that the elderly maintain regular physical activity, and those who are less active are encouraged to gradually increase their activity levels according to their ability to reduce the risk of hypertension and improve overall health. Keywords: Physical Activity; Hypertension Incidence; Elderly Pendahuluan: Hipertensi dikenal sebagai “silent killer” karena sering tidak bergejala namun dapat menimbulkan komplikasi fatal seperti stroke, serangan jantung, dan gagal ginjal. Data Kementerian Kesehatan RI tahun 2023 menunjukkan bahwa hipertensi merupakan penyebab kematian keempat tertinggi di Indonesia, menyumbang 10,2% dari total kematian. Lansia merupakan kelompok yang paling rentan terhadap hipertensi, khususnya di daerah pedesaan. Salah satu faktor yang berkontribusi terhadap meningkatnya kejadian hipertensi pada lansia adalah rendahnya tingkat aktivitas fisik, yang berdampak negatif terhadap fungsi kardiovaskular dan metabolisme tubuh. Tujuan: Untuk mengetahui hubungan aktivitas fisik dengan kejadian hipertensi pada lansia di Desa Dadapbong Sendangsari Pajangan Bantul. Metode: Penelitian kuantitatif dengan desain Deskriptif Kolerasi menggunakan pendekatan Cross Sectional. Populasi penelitian lansia di Desa Dadapbong Sendangsari Pajangan Bantul, sampel di ambil dengan Teknik sampel random sampling sehingga jumlah sampel sebanyak 81 orang. Data dikumpulkan dengan menggunakan kuesioner aktivitas fisik (GPAQ) Global Physical Activity Questionnaire dan juga sphygmomanometer untuk mengetahui tekanan darah resonden. Uji analisis data menggunakan uji non-parametrik Kendall Tau. Hasil: Hasil uji statistik menggunakan uji Kendall Tau menunjukan p-value < 0,05, yaitu 0,000 untuk uji aktivitas fisik dengan kejadian hipertensi. Simpulan: Ada hubungan yang bermakna antara aktivitas fisik dengan kejadian hipertensi pada lansia di Desa Dadapbong Sendangsari Pajangan Bantul. Disarankan lansia untuk menjaga rutinitas aktivitas fisik, dan bagi yang kurang aktif, dianjurkan meningkatkan aktivitas secara bertahap sesuai kemampuan untuk menurunkan risiko hipertensi dan meningkatkan kesehatan. Kata kunci: Aktivitas Fisik; Kejadian Hipertensi; Lansia